Christian Ecclesiology and the Composition of Leviathan: A Newly Discovered Letter To Thomas Hobbes - Collins, Jeffrey R. (The historical journal, 2000)
This communication presents a newly discovered letter to Thomas Hobbes. It offers conclusive evidence that the letter was written by Hobbes's friend, the scientist and Anglican clergyman Robert Payne, and strong evidence that the letter was in fact received by Hobbes in late 1649. The discovered letter was part of a running controversy over questions of church government in which Hobbes and Payne engaged during the composition of Leviathan. In it Payne tries unsuccessfully to soften Hobbes's strident Erastianism, and to defend the beleaguered Church of England from his criticisms. The letter thus sheds light on the political and religious context in which Leviathan was composed. Moreover, the letter offers an indirect but intriguing glimpse at underlying assumptions of Hobbes's religious thought.